Out-of-hospital cardiac arrests in young adults in Melbourne, Australia-Adding coronial data to a cardiac arrest registry - Deasy, C.; Bray, Janet; Smith, K.; Harriss, L.; Bernard, S.; Cameron, P. (2011)
Aim: We aim to describe the coronial findings of young adults where the out-of-hospital cardiac arrest (OHCA) aetiology was 'presumed cardiac'. Methods: Presumed cardiac aetiology OHCAs occurring in young adults aged 16-39 years were identified using the Victorian Ambulance Cardiac Arrest Registry (VACAR) and available coronial findings reviewed. Results: We identified 841 young adult OHCAs where the Utstein aetiology was 'presumed cardiac'. Of these 740 died and 572 (77%) OHCAs were matched to coroner's findings. On review of the coroner's cause of death, 230 (40.2%) had a 'confirmed cardiac' aetiology, 221 (38.6%) were proven 'non-cardiac', 97 (17%) were inconclusive and 24 (4.2%) cases remained 'open'.'Confirmed cardiac' causes of OHCA were ischemic heart disease (n=126, 55%), cardiomegaly (n=26, 11.3%), cardiomyopathy (n=25, 11%), congenital heart disease (n=15, 6.5%), cardiac tamponade due to dissecting thoracic aorta aneurysm (n=10, 4.3%), myocarditis (n=8, 3.5%), arrhythmia (n=7, 3%), others (n=13, 5.7%).'Non-cardiac' causes of OHCA were epilepsy/sudden unexplained death in epilepsy (SUDEP) (n=56, 25%), pulmonary embolism (n=29, 13%), subarachnoid haemorrhage (n=17, 7.7%), other intracranial bleed (n=7, 3.2%), pneumonia (n=17, 7.7%), DKA (n=16, 7.2%), other complications of diabetes mellitus (n=8, 3.6%), complications of obesity (n=9, 4%), haemorrhage (n=12, 5.4%), sepsis (n=8, 3.6%), peritonitis (n=6, 2.7%), aspiration (n=6, 2.7%), renal failure (n=5, 2.3%), asthma (n=5, 2.3%), complications of anorexia (n=3) and alcohol abuse (n=2), thyrotoxicosis (n=2), meningitis (n=1) and others (n=12).Compared with coroner's diagnosed 'non-cardiac' OHCAs, 'confirmed cardiac' were more likely to be witnessed (41% vs 23%, p=. 0.01), receive bystander CPR (35% vs 20%, p=. 0.001), have a shockable rhythm (27% vs 6.3%, p<0.001) and have EMS attempted resuscitation (62% vs 44%, p<0.001). Discussion: Linking OHCA registries with coronial databases for aetiology of the arrest will improve the quality of the data and should be considered by all OHCA registries, particularly for young adult OHCA. © 2011 Elsevier Ireland Ltd.